UTILITY OF THE INTARAN MARKET IN THE CONTINUITY OF MICRO AND SMALL BUSINESSES TYPICAL OF BULELENG DISTRICT PRODUCTS - Ni Komang Deviana (UHN IGB Sugriwa Denpasar, 2024)
The Buleleng Regency, located in the Province of Bali, Indonesia, is known for its unique and diverse range of products. Micro, Small, and Medium Enterprises (MSMEs) are the backbone of the local economy, and the sustainability of these Micro, Small, and Medium Enterprises (MSMEs) depends heavily on various factors, including the intaran market. The intaran market serves as a showcase for displaying and marketing products of Micro, Small, and Medium Enterprises (MSMEs) and the creative economy located in Bengkala Village, Kubutambahan District, Buleleng Regency, Bali. The intaran market operates every Sunday and offers a wide variety of processed goods, handicrafts, creative products, and rarely found foods. The intaran market operates within a smaller geographic scope and plays a significant role in the local economic ecosystem. This research is supported by data collection techniques such as observation, interviews, and documentation, and uses a qualitative descriptive approach to explore and understand how the local market influences the continuity of Micro, Small, and Medium Enterprises (MSMEs) producing typical products of Buleleng Regency.